A meta-analysis of cyclosporine treatment for Stevens–Johnson syndrome/toxic epidermal necrolysis - Ng QX; De Deyn MLZQ; Venkatanarayanan N; Ho CYX; Yeo WS (Dove Medical Press, 2018)
Qin Xiang Ng,1,2 Michelle Lee Zhi Qing De Deyn,3 Nandini Venkatanarayanan,4 Collin Yih Xian Ho,2 Wee-Song Yeo,5 1Department of Medicine, National University Hospital, National University Health System, Singapore; 2MOH Holdings Pte Ltd, Singapore; 3Department of Medicine, James Cook University Hospital, Middlesbrough, UK; 4Department of Medicine, Nottingham University Hospitals NHS Trust, Queen’s Medical Centre, Nottingham, UK; 5Department of Paediatrics, National University Hospital, National University Health System, Singapore Background: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are dermatologic emergencies with high morbidity and mortality risk. Cyclosporine, an immunomodulatory agent, is sometimes used off-label, and its role continues to be debated. This meta-analysis aimed to provide an update of current evidence and to clarify the role of cyclosporine in SJS/TEN treatment better.Methods: Using the keywords [cyclosporine OR cyclosporine OR ciclosporin OR CsA] AND [Steven-Johnson OR SJS OR toxic epidermal OR epidermal necrolysis OR TEN OR hypersensitivity OR dermatologic OR burns], a preliminary search on the PubMed, Ovid, Web of Science, and Google Scholar Database yielded 615 papers published in English between January 1, 1960 and July 1, 2017. The inclusion criteria for this review were: 1) published retrospective or prospective study (excluding single case reports); 2) patients with clinical diagnosis of SJS or TEN; 3) trial of cyclosporine treatment; and 4) available survival/mortality data.Results: A total of 12 studies, with a total of 358 SJS/TEN patients were reviewed. Two studies were excluded from the meta-analysis as they did not report SCORe of toxic epidermal necrosis/predicted mortality data; one was excluded because of possible data irregularities. Meta-analysis of nine studies revealed a significant reduction in mortality risk with cyclosporine therapy (standardized mortality ratio 0.320; 95% CI: 0.119–0.522; P=0.002). Cyclosporine was also generally well tolerated with little adverse effects or increased infection, albeit the patients tended to be critically ill. Publication bias was observed in the funnel plot and Egger test (P=0.0467).Conclusion: Currently available evidence are predominantly open trials and retrospective studies with a significant risk of bias, perhaps owing to the rarity and life-threatening nature of the condition. Given its immunomodulatory actions, cyclosporine could be a potential treatment option for SJS/TEN in addition to best supportive measures. Further confirmation with robust randomized, controlled trials or larger case series is necessary and should be encouraged. Keywords: SJS, TEN, epidermal necrolysis, cyclosporine, CsA, meta-analysis